Effectiveness of E-Modules in Mathematics Learning in Junior High School: A Systematic Literature Review - Ningrum, Sri Adiningsih Utami; Slamet, Isnandar; Fitriana, Laila Nur; Hasanah, Nur (Proceeding International Conference on Mathematics and Learning Research, 2024)
This study aims to identify and analyze publications on the effectiveness of E-modules in learning mathematics in junior high schools based on research journal articles in the last five years, from 2019 to 2024. The systematic literature review method was used with the guidance of the PRISMA diagram. Data were obtained from 246 articles from ERIC, Scopus, and Sinta databases. After screening, 11 articles were found that met the criteria as samples. The findings of this study indicate that E-modules are effective in learning mathematics in junior high school. The characteristics of E-modules include aspects of self-instruction, self-contained, stand-alone, adaptive, user-friendly, interactive, and self-regulated. Mathematical skills or knowledge that are often researched are learning outcomes. Future research should investigate the effectiveness of E-modules in other mathematics skills or knowledge.